Scalable and Intelligent Centralized Alerting Frameworks for Multi-Region Cloud Environments - Praveen Kumar Reddy Gujjala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
As cloud adoption accelerates across enterprise environments, organizations increasingly face the complexity of managing large-scale, distributed systems spanning multiple regions and accounts. The challenge of maintaining effective monitoring and alerting mechanisms across such vast infrastructures has become paramount for ensuring system reliability, security, and performance. This paper presents a comprehensive investigation into the implementation of centralized alerting frameworks within cloud environments, with particular emphasis on Amazon Web Services (AWS) cloud-native tools including CloudWatch, Simple Notification Service (SNS), and Lambda, alongside third-party monitoring solutions such as New Relic and Splunk. The centralized approach to alerting addresses the inherent complexities of distributed cloud architectures by consolidating alert management, reducing operational overhead, and improving response times to critical system events. Through systematic analysis of architectural patterns, implementation strategies, and best practices, this research demonstrates how organizations can achieve scalable, resilient, and cost-effective alerting solutions. The paper examines multi-region deployment strategies, distributed processing mechanisms, and high-availability patterns that ensure continuous monitoring capabilities even during regional service disruptions. Performance evaluation and case study analysis reveal significant improvements in mean time to detection (MTTD) and mean time to resolution (MTTR) when compared to traditional decentralized alerting approaches.
Keywords: Cloud Computing; Centralized Alerting; AWS CloudWatch; Monitoring; Distributed Systems; High Availability